Port governance and sustainable development: The impact of port smartization on port carbon emission efficiency - Zhang, Chaohui; Yang, Yuxue; Wang, Nianxin (Ocean & coastal management, 2024)
Considering the growing volume of seaborne trade worldwide, most ports need smart policies to address high carbon emissions. As a major shipping nation, China is committed to reducing port carbon emissions. China recently introduced a series of smartization policies to accelerate the construction of smart ports, but their effectiveness in energy saving and emission reduction is unclear. Taking 39 major ports in China as research subjects, this study uses the super-efficiency SBM model to measure carbon emissions and the generalized difference-in-differences method to deeply explore the impact of port smartization policies on port carbon emission efficiency. Results indicate that these policies have significantly improved the carbon emission efficiency of ports, a conclusion validated through multiple robustness tests. Heterogeneity analyses show that ports in coastal areas, and in cities with larger populations or moderate economic development, are more significantly affected by port smartization initiatives. Mechanism analysis suggests that the number of port berths, the length of wharves, and container throughput are important channels through which smart port policies influence carbon emission efficiency. This research enriches carbon emission efficiency literature, offers insights for developing countries on reducing emissions and achieving carbon neutrality, and provides a basis for China's smart port construction.